Correction to: Optimisation on pretreatment of kapok seed (Ceiba pentandra) oil via esterification reaction in an ultrasonic cavitation reactor (Biomass Conversion and Biorefinery, (2017), 7, 1, (91-99), 10.1007/s13399-016-0207-9) - Chuah, L.F. (Springer Science and Business Media Deutschland GmbH, 2021)
In this article, reference 9 was incorrect. The original article has been corrected. Â© 2021, Springer-Verlag GmbH Germany, part of Springer Nature.